Comparative Study of Samagandha Rasasindoora (Red Mercuric Sulphide) and Hinguliya Rasasindoora - Lagad, C. E.; Jadhav, V. R.; Bhoyar, M. S. (Asian Journal of Pharmaceutical Research and Development, 2013)
Rasashastra has an unique importance in the field of Ayurveda. It basically deals with the pharmaceutics and therapeutics of drugs of mineral and metallic origin. Kupipakwa Rasayana is commonly used and most potent formulation. Rasasindoora is the drug of choice in many ailments and is commonly used by Rasavaidyas. While reviewing Rasa classics different formulations of Rasasindoora preparation is found with slight differences in ingredients, manufacturing procedures etc. In this study Rasasindoora has been prepared by following two different references of Rasatarangini one is Samagandha Rasasinoora Nirman(SGR)[1] and other is Hinguliya Rasaindoora Nirman.(HGR)[2] The preparatory procedure of both the formulations have been compared to find the differences. Moreover to assess the quality of prepared medicines both the samples were subjected to same Ayurvedic as well as Modern Parameters and results obtained were evaluated to find out disparity. The pharmaceutical procedures of Hinguliya Rasasindoora requires less time duration and manpower than Samaguna Rasasindoora. The Organoleptic characters and values of Physicochemical analysis of both samples are found almost identical.